2014
DOI: 10.1002/hon.2136
|View full text |Cite
|
Sign up to set email alerts
|

Biweekly THP‐COP therapy for newly diagnosed peripheral T‐cell lymphoma patients

Abstract: Pirarubicin tetrahydropyranyl adriamycin (THP-ADR) is an analogue of doxorubicin. This agent exhibits activity against some doxorubicin-resistant cell lines. We performed a phase II study of biweekly THP-COP [50 mg/m(2) pirarubicin, 750 mg/m(2) cyclophosphamide, 1.4 mg/m(2) vincristine (2.0 mg maximum) on day 1, and 100 mg/body predonisolone on days 1-5] in patients with peripheral T-cell lymphoma (PTCL). Seventeen patients with newly diagnosed PTCL were enrolled. Histological diagnoses were of PTCL, not other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…Hence, we could not simply compare our results with those of the JGTLE study. Tomita et al reported that biweekly THP‐COP therapy was a safe and promising therapy for patients with PTCL‐NOS and AITL (CR rate, 88%; 3 year‐OS, 75%) by a prospective phase II study . These results seem to be superior to our results.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Hence, we could not simply compare our results with those of the JGTLE study. Tomita et al reported that biweekly THP‐COP therapy was a safe and promising therapy for patients with PTCL‐NOS and AITL (CR rate, 88%; 3 year‐OS, 75%) by a prospective phase II study . These results seem to be superior to our results.…”
Section: Discussioncontrasting
confidence: 67%
“…Furthermore, the Japanese Clinical Study Group of THP Lymphomas in the Elderly (JGTLE) reported that elderly T‐cell lymphomas had a significantly better response to THP‐COP than to CHOP, whereas no such difference was observed in B‐cell lymphoma . In addition, Tomita et al recently reported encouraging results of a phase II study of THP‐COP therapy for newly diagnosed PTCL patients . However, this phase II study was a single arm trial of THP‐COP and consisted of a small number of cases ( n = 17) including only five PTCL‐NOS.…”
Section: Introductionmentioning
confidence: 99%
“…The PTCL subtypes were PTCL, NOS (39 patients) and AITL (39 patients). The primary treatment regimens were cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP; 14 patients); pirarubicin, cyclophosphamide, vincristine, and prednisone (THP‐COP; 44 patients); THP‐COP followed by radiotherapy (three patients); up‐front autologous peripheral blood stem cell transplantation (three patients); and THP‐COP at 2‐week intervals in a clinical trial (14 patients) . The median serum ferritin level was 183 ng/mL (range, 5–14 622 ng/mL).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the treatment was switched to chemotherapy. Though CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisolone) [5] is the most common chemotherapy regimen, we decided to use THP-COP (pirarubicin, cyclophosphamide, vincristine, and prednisolone) for its proven superior efficacy. Pirarubicin (THP) is an analogue of doxorubicin [5].…”
Section: Case Presentationmentioning
confidence: 99%
“…Though CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisolone) [5] is the most common chemotherapy regimen, we decided to use THP-COP (pirarubicin, cyclophosphamide, vincristine, and prednisolone) for its proven superior efficacy. Pirarubicin (THP) is an analogue of doxorubicin [5]. Significant improvement was noticed after three cycles of chemotherapy, with partially recovery of ptosis, eye movements, and decreased pupil diameters (Fig.…”
Section: Case Presentationmentioning
confidence: 99%